2022
DOI: 10.24016/2022.v8.289
|View full text |Cite
|
Sign up to set email alerts
|

Academic self-efficacy as a protective factor for the mental health of university students during the COVID-19 pandemic

Abstract: Background: University students are vulnerable to developing mental health problems due to constant exposure to academic demands. A situation that has been exacerbated by the COVID-19 pandemic and observed in several recent studies. Therefore, current practices require further research and identification of potentially protective factors for mental health. Objective: This study aimed to analyze academic self-efficacy as a protective factor against depression, anxiety, and stress in university students. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…As for academic self-efficacy, the findings confirm that there is indeed an inverse relationship with general distress, which is consistent with previous evidence ( Alemany-Arrebola et al, 2020 ; Ampuero et al, 2022 ; Andersson et al, 2022 ; Carranza et al, 2022 ). A previous study conducted in Peru by Ampuero et al (2022) found that one third of university students surveyed during confinement presented severe to extremely severe symptoms of depression, anxiety and stress and that academic self-efficacy worked as a protective factor with a moderate effect, as it allowed university students to be aware and confident of their own skills and abilities in different academic activities.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…As for academic self-efficacy, the findings confirm that there is indeed an inverse relationship with general distress, which is consistent with previous evidence ( Alemany-Arrebola et al, 2020 ; Ampuero et al, 2022 ; Andersson et al, 2022 ; Carranza et al, 2022 ). A previous study conducted in Peru by Ampuero et al (2022) found that one third of university students surveyed during confinement presented severe to extremely severe symptoms of depression, anxiety and stress and that academic self-efficacy worked as a protective factor with a moderate effect, as it allowed university students to be aware and confident of their own skills and abilities in different academic activities.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, general distress was found to be inversely related to resilience, social support, and academic self-efficacy. These findings reinforce the importance of working on coping strategies to deal with distress ( Ampuero et al, 2022 ; Andersson et al, 2022 ; Noh and Park, 2022 ; Ortiz-Calvo et al, 2022 ); considering that resilience presents an inverse relationship with general distress and a direct relationship with psychological well-being ( Beckstein et al, 2022 ; Calle and Urigüen, 2022 ; Nuñez and Vásquez, 2022 ; Valero et al, 2022 ; Xiao et al, 2023 ). This is complemented by the study of Li et al (2021) , who found that in the first weeks of confinement resilience functioned as a protective factor for mental health and that, when resilience is studied as a trait, social support serves as a buffer factor for the impact of low levels of resilience on mental health.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations